(untitled) (Research, Society and Development, 2020)
Ziziphus joazeiro is endemic to the brazilian Caatinga and its fruits can be used as a food supplement by accelerating the ethanol metabolism in the body and reducing the alcohol harmful effects due to high alcohol dehydrogenase (ADH) activity. The objective was to determine the kinetics of ADH activity, in different incubation times, of Z. joazeiro mature fruits as a food supplement. Ziziphus joazeiro fruits, at the fourth maturation stage, were incubated for 0 (no incubation), 3, 6, 12, 24 and 48 hours at room temperature. The ADH activity was determined. ADH activity was higher in fruits incubated for 0 and 3 h. The ADH activity was higher in the early incubation times, probably due to the greater availability of NAD+, which after being reduced to NADH delayed regeneration. Without the cofactor in the oxidized form, the enzymatic activity decreases. Ziziphus joazeiro fruit has the potential to be used as a food supplement accelerating the alcohol metabolism and reducing the harmful effects.